Digital Transformation in Education: Examining the Contribution of Madrasah Principal Leadership to Teacher Teaching Performance (EDUKASIA, 2023)
This article investigates the influence of madrasah principal leadership on the madrasah teachers' teaching performance in the digital era. The study used a quantitative approach, and the survey method involved 124 respondents randomly selected from seven madrasahs in Jepara, Indonesia, based on cluster techniques. The results revealed that the F-test obtained F-statistic> F-table (39.824 > 3.07) and significance (0.000 < 0.05), indicating that the leadership of the madrasah principal exerted a positive and significant influence on the madrasah teacher's performance. The coefficient of determination test results exhibited an R Square (R2) value of 0.240, meaning that teacher teaching performance is influenced by the leadership variable of the madrasah principal by 24% and 76% by other variables. These findings provide a foundation for understanding the critical role of madrasah principal leadership in improving teacher-teaching performance. Further research is recommended to consider the factors affecting teaching performance and expansion.